Long-term outcomes of dasatinib-induced pulmonary arterial hypertension: a population-based study. Issue 1 (27th July 2017) - Weatherald, Jason; Chaumais, Marie-Camille; Savale, Laurent; Jaïs, Xavier; Seferian, Andrei; Canuet, Matthieu; Bouvaist, Hélène; Magro, Pascal; Bergeron, Anne; Guignabert, Christophe; Sitbon, Olivier; Simonneau, Gérald; et al.
This study aimed to describe the long-term outcomes of pulmonary arterial hypertension (PAH) induced by dasatinib. 21 incident, right heart catheterisation-confirmed cases of dasatinib-induced PAH were identified from the French Pulmonary Hypertension Registry. Clinical and haemodynamic variables were compared from baseline to last follow-up (median (range) 24 (1–81) months). Median age was 52 years and 15 patients were female (71%). 19 patients received dasatinib for chronic myelogenous leukaemia for a median (range) duration of 42 (8–74) months before PAH diagnosis. No bone morphogenic protein receptor-2 ( BMPR2 ) mutations were found in the 10 patients tested. Dasatinib was uniformly discontinued and 11 patients received PAH medications. Four patients died during follow-up. New York Heart Association functional class improved from 76% in class III/IV to 90% in class I/II (p<0.01). Median (range) 6-min walk distance improved from 306 (0–660) to 430 (165–635) m (p<0.01). Median (range) mean pulmonary arterial pressure improved from 45 (30–70) to 26 (17–50) mmHg (p<0.01) and pulmonary vascular resistance from 6.1 (3.2–27.3) to 2.6 (1.2–5.9) Wood units (p<0.01). Patients treated with PAH medications had worse baseline haemodynamics but similar long-term outcomes to untreated patients. PAH persisted in 37% of patients. Dasatinib-induced PAH frequently improves after discontinuation but persisted in over one-third of patients, therefore systematic follow-up is essential. Dasatinib-induced pulmonary arterial hypertension persists in over one-third of patients despite stopping dasatinib http://ow.ly/xRPt30csyk9